Identification of Single Nucleotide Polymorphism Associated with Type 2 Diabetes Mellitus in Korean Population - Bayarjavkhlan Ch.; (NbAQRVAWHLAN ~(B.s (2008)
(NtOW^ HURAANGUJs
References P.38-41.
Keywords: (N^IHRIJN [IVIN H\W [INV (B2s; (NDIABETs; 9